2019 IEEE 8th Joint International Information Technology and Artificial Intelligence Conference (ITAIC) 2019
DOI: 10.1109/itaic.2019.8785563
|View full text |Cite
|
Sign up to set email alerts
|

Texture features based microscopic image classification of liver cellular granuloma using artificial neural networks

Abstract: Automated classification of Schistosoma mansoni granulomatous microscopic images of mice liver using Artificial Intelligence (AI) technologies is a key issue for accurate diagnosis and treatment. In this paper, three grey difference statistics-based features, namely three Gray-Level Co-occurrence Matrix (GLCM) based features and fifteen Gray Gradient Co-occurrence Matrix (GGCM) features were calculated by correlative analysis. Ten features were selected for three-level cellular granuloma classification using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Using other specialized software like Strataquest ( TissueGnostics StrataQuest, 2021 ) and Cell Profiler ( Mcquin et al, 2018 ) it is then possible to identify mechanistic reasons for observed branching in pseudotime. In parallel, classification of ROIs in branched trajectories can be used to label ROIs for training convolutional neural networks to identify such clusters in routinely stained images ( Shi et al, 2019 ). These can be used as a powerful research or diagnostic tool ( Figure 1.4b ).…”
Section: Downstream Analysis Of Multi-omics Datamentioning
confidence: 99%
“…Using other specialized software like Strataquest ( TissueGnostics StrataQuest, 2021 ) and Cell Profiler ( Mcquin et al, 2018 ) it is then possible to identify mechanistic reasons for observed branching in pseudotime. In parallel, classification of ROIs in branched trajectories can be used to label ROIs for training convolutional neural networks to identify such clusters in routinely stained images ( Shi et al, 2019 ). These can be used as a powerful research or diagnostic tool ( Figure 1.4b ).…”
Section: Downstream Analysis Of Multi-omics Datamentioning
confidence: 99%